ANALISIS PEMELIHARAAN SYRINGE PUMP DI.LAB TERPADU UNIVERSITAS SARI MUTIARA INDONESIA - Mhd. Rafli Perdana; Siti Rahmah (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2021)
Medical devices are divices that are always in a ready to use condition and can function properly. This requires the Sari Mutiara University Integrated Laboratory to assist and medical equipment as effectively and efficiently as possible. This study aims to look at the syringe pump monitoring system in the USM-Indonesia Integrated Lab.Descriptive research method. Syringe pump tools and materials, questionnaire instruments used to conduct direct interviews with officers in the integrated laboratory, observation and documents.The results of this study indicate that all medical equipment including the syringe pump in the USM-Indonesia integrated Lab has never been maintained because there has not been a maintenance program for the medical equipment in the Lab. Integrated suggestions for syringe pump equipment and other health equipment to be maintained in the form of heating the appliance twice a week so that the tool is always in a condition that can function properly and has a longer service life, it is necessary to make SOP for operating the syringe pump tool and other tools.